Affections, market and contemporary masculinities: preliminary notes of a research on mobile applications for affective/sexual relationships - Pelucio, Larissa [UNESP] (Univ Sao Carlos, Dept Sociology Federal, 2016)
This article presents a methodological discussion from preliminary results of a research on contemporary masculinities, technologies and affections whose investigation field is focused on two mobile applications for romantic/sexual relationships from which men born between 1945 and 1986 are taken as collaborators. The online ethnography is combined with the analysis of the emergence of a new emotional ethics associated with sexual and romantic contemporary market which takes the studies on gender and sexuality, digital media and subjectivities in a socio-anthropological perspective as a theoretical reference.
Keywords: mobile applications; contemporary masculinities; happn; Adote um Cara; sexuality; online research methodology